Study on the characteristics of hydrate formation in HSB solution: Focused on the micro-morphologies. (1st April 2022) - Liu, Zhiming; Li, Yuxing; Wang, Wuchang; Song, Guangchun; Yu, Xinran; Li, Zhigang; Wang, Honghong; Xiao, Wensheng; Wang, Hongyan
Abstract: Hydrate formation could be promoted by the surfactant solutions significantly, so the study of its characteristics is helpful to the industrial application of hydrate-based technologies. In this study, using Alkyl C16-18 hydroxypropyl sulfobetaine (HSB1618) solution, the hydrate formation in the liquid film, on the gas bubble surface were investigated, and the micro process of the liquid phase migration between the hydrate particles was intuitively exhibited. The mechanisms of the hydrate particle burst and the presence of concentric lines were proposed. The results showed that on the reactor wall, hydrate spots were formed in the liquid film, the liquid phase could migrate upward through the pores inside the hydrate spots under the capillary force to sustain the further hydrate growth. When the hydrate particles were initially formed, they were hexagonal pyramid-shaped and with their vertex towards the liquid phase, with the hydrate particles grew bigger, they burst into fragments, then the hydrate film was observed to be formed by the tight aggregation, thickening, and growth of the fragments in the liquid film. The heterogeneous nucleation could reduce the energy barrier for the hydrate formation, which facilitated the hydrate formation on the reactor wall. Highlights: A high-speed camera was used for the micro-morphology of the formed hydrate. The micro-morphologies of hydrate particles were discussed detailly. The formation and dissolution of the hydrate film on gas bubble was observed. Micro process of liquid phase migration between hydrate spots was intuitively exhibited. Mechanisms for the hydrate particle burst and the concentric lines were proposed.